2022
DOI: 10.3389/fmolb.2022.978663
|View full text |Cite
|
Sign up to set email alerts
|

Exported J domain proteins of the human malaria parasite

Abstract: The heat shock protein 40 (Hsp40) family, also called J domain proteins (JDPs), regulate their Hsp70 partners by ensuring that they are engaging the right substrate at the right time and in the right location within the cell. A number of JDPs can serve as co-chaperone for a particular Hsp70, and so one generally finds many more JDPs than Hsp70s in the cell. In humans there are 13 Hsp70s and 49 JDPs. The human malaria parasite, Plasmodium falciparum, has dedicated an unusually large proportion of its genome to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Parasite protein export through the parasitophorous vacuolar membrane into the host erythrocyte occurs in an unfolded state, necessitating the assistance of chaperones to maintain their translocation competence and aid in folding [11,12]. Only one PfHSP70 chaperone is exported [17], but it is not vital for parasite growth [22], leading researchers to believe that the parasite may utilize the host HSP70 chaperone for protein folding and host erythrocyte remodeling [23]. Since the JDPs can modulate HSP70 protein activity, our lab targets the putative JDPs of P. falciparum that have a propensity to get exported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parasite protein export through the parasitophorous vacuolar membrane into the host erythrocyte occurs in an unfolded state, necessitating the assistance of chaperones to maintain their translocation competence and aid in folding [11,12]. Only one PfHSP70 chaperone is exported [17], but it is not vital for parasite growth [22], leading researchers to believe that the parasite may utilize the host HSP70 chaperone for protein folding and host erythrocyte remodeling [23]. Since the JDPs can modulate HSP70 protein activity, our lab targets the putative JDPs of P. falciparum that have a propensity to get exported.…”
Section: Discussionmentioning
confidence: 99%
“…Among the P. falciparum chaperones, only a subset of PfHSP40 (P. falciparum Heat Shock Protein 40) family proteins (18 out of 49) have the PEXEL motif [12][13][14]. Members of the HSP40 family, alternatively referred to as J-domain proteins (JDPs) [15], function as co-chaperones, facilitating the delivery of unfolded polypeptides to the cognate HSP70 proteins for folding and stimulating the ATPase activity [12]. JDPs are categorized into four types based on their canonical regions: J-domain, glycine-rich region, cysteine-rich zinc-binding domain, and C-terminal domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 50 In the parasite, many of the exported PfHSP40s are expressed during the early stages of the asexual phase of the malaria parasite life cycle, and they are vital for malaria protein export and survival during febrile episodes. 51 , 52 , 53 Some of these exported PfHSP40s have been confirmed to functionally interact with the only exported PfHSP70, PfHSP70-x. For example, Daniyan et al 54 and Dutta et al 36 found compelling evidence that the exported type II PfHSP40s, PFA0660w and PFE0055c have a functional association with PfHSP70-x.…”
Section: Malarial Hsps and Their Complexes As Drug Targetsmentioning
confidence: 93%
“…To explore this idea, key differences in the PPIs between P. falciparum and human cochaperone–chaperone complexes have been revealed based on structural analyses. 36 , 53 , 60 , 61 , 62 , 63 Furthermore, molecular docking studies have compared PfHSP70–PfHSP40 complexes to their human HSP70–HSP40 equivalents, and used these complexes to screen drug repurposing small molecule libraries to identify compounds with preferential binding to the malarial over the human system. 64 As expected, the J domain–NBD interfaces of PfHSP70-x–PFE0055c and human HSP70 (HSPA1A)-DNAJA1 both involved multiple topologically equivalent hydrogen bond interactions between highly conserved positively charged J domain helix II residues and NBD negatively charged residues ( Figure 2 ).…”
Section: Malarial Hsps and Their Complexes As Drug Targetsmentioning
confidence: 99%